A Study on Microwave Absorption Properties of Carbon Black and Ni0.6Zn0.4Fe2O4 Nanocomposites by Tuning the Matching-Absorbing Layer Structures - Ibrahim I.R.; Matori K.A.; Ismail I.; Awang Z.; Rusly S.N.A.; Nazlan R.; Mohd Idris F.; Muhammad Zulkimi M.M.; Abdullah N.H.; Mustaffa M.S.; Shafiee F.N.; Ertugrul M. (Nature Research, 2024)
Indexed by WOS/SCOPUS/ERA